Evaluation of Intra-Arterial Nimodipine Therapy in Post-Subarachnoid Hemorrhage Refractory Cerebral Vasospasm - Jain, Shrey; Sinha, Ajit K; Goyal, Sumit (Cardiology and Cardiovascular Medicine, 2022)
Background: Cerebral vasospasm is a major cause of morbidity and mortality in patients with subarachnoid hemorrhage. Vasospasm is managed with triple H and vasodilators but sometimes, patients do not respond. Intra-arterial vasodilator infusion has been shown to improve outcome in such patients. In this study, we try to evaluate the efficacy of intra-arterial nimodipine therapy in 43 patients of post-aneurysmal subarachnoid hemorrhage refractory cerebral vasospasm. Methods: It is a prospective observational study of a group of 43 patients presenting with refractory cerebral vasospasm as per the inclusion criteria. Pre-procedure neurological assessment and Transcranial Doppler (TCD) monitoring were done. Endovascular spasmolysis was conducted and post-operative morbidity and outcomes were noted. Follow up of the patients was done at the time of discharge and at 6 months according to the Modified Rankin Scale and NCCT head. Results: Most of the patients developing refractory cerebral vasospasm belonged to Hunt and Hess Grade 2 and 3 and Fisher grade 3 and 4. 87.5% of the patients showed clinical recovery following endovascular spasmolysis and 58% of the patients showed complete angiographic recovery. Outcome after 6 months was good in 76%, moderate in 12% and poor in 12% patients. NCCT head showed no infarct in 58%, minor infarct in 28% and major vascular territorial infarct in 14% patients. Conclusion: Intra-arterial nimodipine infusion is a safe and effective therapy with minimum risk of complications if adhered to standard endovascular practice. By timely intervention, major ischemic insult to the brain can be averted, thereby significantly improving the prognosis.